The role of microRNAs in learning and long-term memory - L. N. Grinkevich (Вавиловский журнал генетики и селекции)
The mechanisms of long-term memory formation and ways to improve it (in the case of its impairment) remain an extremely difficult problem yet to be solved. Over the recent years, much attention has been paid to microRNAs in this regard. MicroRNAs are unique endogenous non-coding RNAs about 22 nucleotides in length; each can regulate translation of hundreds of messenger RNA targets, thereby controlling entire gene networks. MicroRNAs are widely represented in the central nervous system. A large number of studies are currently being conducted to investigate the role of microRNAs in the brain functioning. A number of microRNAs have been shown to be involved in the process of synaptic plasticity, as well as in the long-term memory formation. Disruption of microRNA biogenesis leads to significant cognitive dysfunctions. Moreover, impaired microRNA biogenesis is one of the causes of the pathogenesis of mental disorders, neurodegenerative illnesses and senile dementia, which are often accompanied by deterioration in the learning ability and by memory impairment. Optimistic predictions are made that microRNAs can be used as targets for therapeutic treatment and for diagnosing the above pathologies. The importance of applications related to microRNAs significantly raises interest in studying their functions in the brain. Thus, this review is focused on the role of microRNAs in cognitive processes. It describes microRNA biogenesis and the role of miRNAs in the regulation of gene expression, as well as the latest achievements in studying the functional role of microRNAs in learning and in long-term memory formation, depending on the activation or inhibition of their expression. The review presents summarized data on the effect of impaired microRNA biogenesis on long-term memory formation, including those associated with sleep deprivation. In addition, analysis is provided of the current literature related to the prospects of improving cognitive processes by influencing microRNA biogenesis via the use of CRISPR/Cas9 technologies and active mental and physical exercises.